West Indian Subterranean Termite, Heterotermes sp. (Insecta: Isoptera: Rhinotermitidae) - Rudolf H. Scheffrahn; Nan-Yao Su (EDIS, 2002)
This document is EENY-127 one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: April 2000.